Overcoming radioresistance in WiDr cells with heavy ion irradiation and radiosensitization by 2-deoxyglucose with photon irradiation - Hasse, Felix; Körber, Stefan A.; Prigge, Elena-Sophie; Liermann, Jakob; Knebel Doeberitz, Magnus von; Debus, Jürgen; Sterzing, Florian (Clinical and translational radiation oncology, 2019)
Background and purpose: Radiosensitizers and heavy ion irradiation could improve therapy for female patients with malignant tumors located in the pelvic region through dose reduction. Aim of the study was to investigate the radiosensitizing potential of 2-deoxy-d-glucose (2-DG) in combination with carbon ion-irradiation (12C) in representative cell lines of cancer in the female pelvic region. - Materials and methods: The human cervix carcinoma cell line CaSki and the colorectal carcinoma cell line WiDr were used. 2-DG was employed in two different settings, pretreatment and treatment simultaneous to irradiation. Clonogenic survival, α and β values for application of the linear quadratic model and relative biological effectiveness (RBE) were determined. ANOVA tests were used for statistical group comparison. Isobolograms were generated for curve comparisons. - Results: The comparison of monotherapy with 12C versus photons yielded RBE values of 2.4 for CaSki and 3.5 for WiDr along with a significant increase of α values in the 12C setting. 2-DG monotherapy reduced the colony formation of both cell lines. Radiosensitization was found in WiDr for the combination of photon irradiation with synchronous application of 2-DG. The same setup for 12C showed no radiosensitization, but rather an additive effect. In all settings with CaSki, the combination of irradiation and 2-DG exhibited additive properties. - Conclusion: The combination of 2-DG and photon therapy, as well as irradiation with carbon ions can overcome radioresistance of tumor cells such as WiDr.
Gesehen am 06.12.2019